The Son's Entrance into the Heavenly World: The Soteriological Necessity of the Scriptural Catena in Hebrews 1.5-14 - Jipp, Joshua W. (New Testament studies, 2010)
Hebrews 1.5-14 has proved difficult to integrate within the author's larger literary project. More recent scholarship has emphasized rightly that the catena centers upon the Son of God's royal enthronement, but the question as to why the author should begin his argument this way has yet to be answered. In this essay I argue that the event which the catena describes, namely the Son's enthronement to the heavenly world, is critical for the entire logic of the author's argument regarding how humanity's salvation is accomplished. The likelihood of this conclusion is bolstered by the rarely recognized inclusio between 1.5-14 and 12.18-29. Finally, I briefly examine four texts which suggest that the author envisions the Son's narrative, particularly his entrance into God's heavenly realm as described in 1.5-14, as a soteriological necessity, and pattern, for humanity.